Klebsiella pneumoniae Lipopolysaccharide O Typing: Revision of Prototype Strains and O-Group Distribution among Clinical Isolates from Different Sources and Countries - Hansen, Dennis S. (American Society for Microbiology, 1999)
We have previously described an inhibition enzyme-linked immunosorbent assay method for the O typing of O1 lipopolysaccharide from Klebsiella pneumoniae which overcomes the technical problems and limitations of the classical O-typing method. In this study, we have extended the method to all of the currently recognized O types. The method was validated by studying the prototype strains that have defined the O groups by the classical tube agglutinatination O-typing method. Based on these results, we confirmed the O types of 60 of 64 typeable strains, and we propose a revised O-antigenic scheme, with minor but necessary changes, consisting of serogroups or serotypes O1, O2, O2ac, O3, O4, O5, O7, O8, and O12. Application of this typing method to 638 K. pneumoniae clinical isolates from Denmark, Spain, and the United States from different sources (blood, urine, and others) showed that up to 80% of these isolates belong to serotypes or serogroups O1, O2, O3, and O5, independently of the source of isolation, and that a major group of nontypeable isolates, representing about 17% of the total, consists of half O(+) and half O(−) strains. Differences were observed, however, in the prevalence of the lipopolysaccharide O types or groups, depending on the country and isolation source.